PENGARUH KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN, DAN LIKUIDITAS TERHADAP KEBIJAKAN DEVIDEN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2020 – 2023 - Dovan Aditya Riswandi; Ediyanto Ediyanto; Lita Permata Sari (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The LQ45 stock index represents 45 companies listed on the Indonesia Stock Exchange (IDX) that are carefully selected based on their high liquidity, large market capitalization, strong fundamentals, and promising growth potential. This index serves as a benchmark for assessing the performance of major and liquid companies in the Indonesian capital market. The purpose of this study is to examine the effect of Managerial Ownership, Company Size, and Liquidity on Dividend Policy, with Financial Performance as an intervening variable in LQ45 companies listed on the IDX. This research applies a quantitative method and utilizes Smart PLS 3.0 (Partial Least Squares) for data analysis to determine the relationships between the variables. The study aims to provide insights into how internal company characteristics and financial performance influence corporate decisions related to dividend distribution within the context of Indonesia’s capital market. The results show that Managerial Ownership (X1) has a significant negative impact on Financial Performance (Y1), while Company Size (X2) exhibits a significant positive effect on Financial Performance (Y1). In contrast, Liquidity (X3) shows a negative but insignificant relationship with Financial Performance (Y1). Furthermore, Managerial Ownership (X1) negatively but insignificantly affects Dividend Policy (Y2), and Company Size (X2) has a positive yet insignificant effect on Dividend Policy (Y2). Liquidity (X3) has a significant negative influence on Dividend Policy (Y2), while Financial Performance (Y1) has a positive but insignificant impact on Dividend Policy (Y2). The indirect effects of Managerial Ownership, Company Size, and Liquidity on Dividend Policy through Financial Performance are all insignificant, suggesting that financial performance does not play a significant mediating role in this relationship.